Wide-band wide-coverage linear array of four semi-circular sector horns - Yang, Lei (2013)
A linear array antenna consisting of four semi-circular sector horns is proposed to achieve wide-band and wide-coverage radiation characteristics. The array can operate over a wide frequency band from 850 MHz to 2570 MHz and cover a wide range of 120° in the azimuth plane. Each semi-circular sector horn is fed by a centred coaxial probe loaded with a conducting cylinder to obtain a wide-band and symmetric radiation pattern of vertical polarization. Measured and simulated results of a designed array show its potential applications for base stations serving wide-range mobile users and other wide-band spectrum-monitoring systems.